(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to analyze the role of educational technological activities in developing students’ scientific inquiry skills through a library-based analytical review of relevant educational literature and previous studies، The study explored the relationship between integrating technological activities into the learning environment and the development of inquiry skills such as observation، problem identification، hypothesis formulation، and data analysis، The analysis indicated that most previous studies focused on measuring the effectiveness of technology-based interventions، while the theoretical analytical understanding of this relationship remained limited، The study proposed a theoretical perspective suggesting that technological activities contribute indirectly to inquiry skill development by enhancing active learning، increasing cognitive interaction، and fostering intrinsic motivation، The study recommended the systematic integration of technological activities into teaching practices، professional development for teachers، and future empirical research to examine the proposed perspective.